Screening fungi for thermostable phytases and comparing the thermostability of a current phytase produced under liquid culture and solid substrate culture conditions - Casey, N.H. (Norman Henry) (University of Pretoria, 2013)
Dissertation (MSc (Agric) Animal Nutrition)--University of Pretoria, 2006.